Gastric pathology in patients with common variable immunodeficiency. Issue 1 (1st July 1999) - Zullo, A; Romiti, A; Rinaldi, V; Vecchione, A; Tomao, S; Aiuti, F; Frati, L; Luzi, G
Abstract : BACKGROUND/AIMS: Common variable immunodeficiency (CVID) is an immunological disorder characterised by defective antibody production. Patients with CVID have a high risk of gastric cancer. It has been suggested that gastric cancer results from an interaction between environmental factors and a genetic predisposition. The role of Helicobacter pylori as an environmental factor in gastric carcinogenesis is of current interest. Moreover, p53 gene mutations have been reported in gastric cancer. This study focuses on the gastric pathology of patients with CVID and correlation with H pylori infection. METHODS: Thirty four consecutive dyspeptic patients with CVID (mean age 49.6 years, range 14–72; 17 men) were included in the study. An upper gastrointestinal endoscopy was performed and biopsy specimens were taken from the antrum, incisura angularis, and gastric body. Biopsies were used for histological assessment, to identify the presence of H pylori, and to evaluate p53 overexpression. RESULTS: H pylori infection was detected in 14/34 (41%) patients. Chronic active gastritis involving both antrum and body was observed more frequently in H pylori positive (79%) than H pylori negative (20%) patients (p = 0.001). Similarly, a histological feature of multifocal atrophic gastritis was found more frequently in infected (50%) than uninfected patients (10%) (p = 0.012). In addition, one case of gastric adenocarcinoma and another of notable dysplasia were observed in the H pylori positive group. Overexpression of p53 was found in six (18%) patients, including one with normal gastric mucosa. CONCLUSIONS: It can be hypothesised that both H pylori and p53 alterations play a role in the gastric carcinogenesis of patients with CVID.